Jubenil Psychogenic Visual Disturbance in Kobari Hospital - HARA, Sonoe; SUDO, Satoko; HASHIMOTO, Tetsuya; HASHIRA, Munetaka; NAGASE, Yoshiko (JAPANESE ORTHOPTIC JOURNAL, 1990)
We tried to visual examination for 1263 children in Noda city and Sekiyado town. We got 29 (2.3%) children with psychogenic visual disturbance in 1263. 21 children were junior school students and 8 children were junior high school students. Then, we made some close investigation into them about ophthalmology and Y-G test. Most popular vision were 24/60 to 36/60 when they were not corrected. 19 (66%) indicated typical disturbance of visual field in 29, but 10 (34%) indicated normal type. All though we could not found sexual differentiation in disturbance of vision of junior school students group, in junior high shool students group only femals were recognized in this study. Y-G test indicated of normal type. At 41% children visual disturbance were caused by some mental blow but the remainder not always concluded by it. We think that juvenile psychogenic visual disturbance is not always cause by mental blow. We think it is likely better that ophthalmology staff study more about juvenile psychology.